MENCIPTAKAN PEMBELAJARAN MATEMATIKA YANG KREATIF DAN MENYENANGKAN - Rahmi, Rahmi (Prodi Pendidikan Matematika, 2013)
The  general  puposes  of  experiencing  math  subject  to  elementary  and  middle  school students are; first preparing the students to face the changing of real life through the thinking  rehearsal  based  on  the  effective,  effisien,  honesty,  critical,  rationale,  and logical  way  of  thinking,  and  second,  preparing  the  students  to  apply  the  mental principle  of  math  in  their  daily  life  and  as  basic  in  learning  other  disciplines. Regarding to the importance of learning this subject, teacher of math should be able to create  an  effective  teaching  learning  process  to  stimulate  and  to  rise  students enthusiasm in learning match. One of the strategy that can increase students desire in learning  math  is  PAILKEM  (Pembelajaran  Aktif,  Inovatif,  Lingkungan,  Kreatif, Efektif, dan Menarik). There is an interactive dialoque between  teacher students and students, during teaching-learning process.This creates a condusive situation in wich students feel free to discuss their problems in learning math to their teachers and their classmates.  At  the  end,  through  this  strategy,  students  can  increase their  ability  in learning  and  it  is  hoped  that  teaching  learning  process  will  be  done  in  optimalachievement.Key word: Learning of mathematic, PAILKEM